Noncovalent microcontact printing for grafting patterned polymer brushes on graphene films - Gao, Tingting (Langmuir : the ACS journal of surfaces and colloids, 2013)
This article describes a simple and universal approach to prepare patterned polymer brushes on graphene-based substrate surfaces by microcontact printing (μCP) of initiator molecules and subsequent surface initiated atom transfer radical polymerization (SI-ATRP) method. Four different initiators are designed and have strong adhesion with graphene-based substrates through noncovalent interaction. Optical and fluorescence microscopy, atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS) were used to characterize the successful polymerization of vinyl monomers on substrate surfaces. To demonstrate the broad applicability of this strategy, polymer brushes with different functionalities including cationic and anionic polyelectrolyte, thermally and pH responsive polymers, as well as polymer patterns on different graphene-based surfaces are fabricated. Binary polymer brushes can also be easily prepared by further initiating the initiator backfilled in the bare areas